Field drought conditions impact yield but not nutritional quality of the seed in common bean (Phaseolus vulgaris L.) - Smith, Millicent R.; Veneklaas, Erik Jan; Polania, Jose; Rao, Idupulapati M.; Beebe, Stephen E.; Merchant, Andrew (Public Library of Science, 2019)
Drought substantially limits seed yield of common bean (Phaseolus vulgaris L.) in the tropics. Understanding the interaction of drought on yield and the nutrient concentration of the seed is vital in order to supply nutrition to the millions of consumers who rely on common bean as a staple crop. Nevertheless, the impact of drought on common bean for both yield and nutrient concentration has not yet been concurrently investigated in a field environment. Using 10 bred lines developed by CIAT and its partners for their improved adaptation to drought and phosphorus deficiency, this study characterised the impact of drought on yield and nutrient concentration for leaf and seed tissue of common bean grown in the field. Drought significantly reduced leaf area (by ~50%), harvest index (by ~60%), yield (by ~70%), seed weight (by ~25%) and enriched carbon isotope abundance (δ13C) in the seed. Within the soluble leaf fraction, drought significantly decreased the concentration of mineral nutrients and amino acids, whereas no negative effect on the concentration of nutrients and amino acids was detected within the seed. Genotypic variation in nutrient concentration in both the leaf and seed tissue was identified and should be explored further to identify traits that may confer tolerance to abiotic stress.